Structural Characteristics and Tectonic Evolution of the Wunansha Uplift in the South Yellow Sea Basin, China. (25th May 2022) - Zhang, Tian; Zhu, Weilin; Fu, Qiang; Fu, Xiaowei
Abstract : By selecting typical seismic sections to carry out detailed structural interpretation, the structural style features of the Wunansha Uplift in the South Yellow Sea basin were systematically combined, and the compressional structures (imbricate, opposite/back thrust, and Y-shaped structures), strike-slip faults (positive flower-shaped faults), and extensional normal faults (listric-shaped normal faults) were identified. On this basis, combined with the characteristics of the regional stress field and the background of deep geodynamics, the genetic mechanism and structural evolution of the structural style in the Wunansha Uplift were defined. The stress mechanism of the compressional structures originated from the initial high-speed and low-angle NW subduction of the paleo-Pacific plate during the early Yanshanian movement in the Early Jurassic. The regional strike-slip fault was mainly a positive flower structure with compression and torsion characteristics, and its stress mechanism originated from sinistral shear caused by the Early Cretaceous low-angle NNW subduction of the paleo-Pacific plate. The Tan-Lu fault in eastern China also had sinistral shear characteristics in this period. The extensional normal fault was characterized by a listric shape, which developed along the northern boundary of the Wunansha Uplift, that is, the connection between the Wunansha Uplift and the Southern Depression of the South Yellow Sea basin. The stress mechanism was derived from the transition of the paleo-Pacific plate from low-angle to high-angle subduction during the late Yanshanian movement in the Late Cretaceous. Simultaneously, the tectonic stress system in eastern China also changed from compressional to tensional.